ANALISIS RESEPSI KHALAYAK MENGENAI ISU STIGMATISASI PADA ODGJ(Studi Pada Viewers Channel Youtube Menjadi Manusia) - Siti Choiriah (2022)
The Youtube channel Menjadi Manusia created the video in concern for people with mental disorders (ODGJ) on their YouTube channel entitled "Stop calling people crazy, ODGJ are also humans". The video seeks to raise a picture of a social phenomenon, especially about the public's negative perceptions of people with mental disorders in Indonesia in terms of the stigma and discrimination that have been attached to people with mental disorders. The Purpose of This study are to find out how the audience's reception regarding the issue of stigmatization of ODGJs, find out the position of audience based on Stuart Hall Model and to find out what factors are behind the audience's reception. This study using a qualitative research approach with Audience Etnographic method with reception analysis. The results of this study showed that the Viewer's different background affecting their receptions in interpreting the issue of stigmatization in people with mental disorders. The audience's perception of the issue is influenced by factors such as education, about mental health issues (Field Of Knowledge), and the experience in interacting in person with ODGJs, as well as being a survivor of mental disorders (Field of Experience). The Viewer's Interpretation is also the result of the learning process obtained by the audience from their environment, family, and the media that they have been consumed. Different experiences of the viewers menjadi manusia youtube channel have made the way they interpret different.